2015
DOI: 10.1016/j.sjbs.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serotyping characterization of shiga toxogenic Escherichia coli associated with food collected from Saudi Arabia

Abstract: Shiga toxin-producing Escherichia coli (STEC) strains are considered as one of the major food-borne disease agents in humans worldwide. STEC strains, also called verotoxin-producing E. coli strains. The objectives of the present study were serotyping and molecular characterization of shiga toxigenic E. coli associated with raw meat and milk samples collected from Riyadh, Saudi Arabia. A total of 540 milk samples were collected from 5 dairy farms and 150 raw meat samples were collected from different abattoirs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
7
16
0
Order By: Relevance
“…Almost one third (28.9%) of the examined bovine milk in this study showed the existence of either or both E. coli or S. aureus pathogens. E. coli was detected in 13.2% of the examined milk samples, which was comparable with previous report (15.9%) in Saudi Arabia [24]. Higher prevalence was recorded in Ethiopia (29.6%) by Garedew et al [4].…”
Section: Discussionsupporting
confidence: 87%
“…Almost one third (28.9%) of the examined bovine milk in this study showed the existence of either or both E. coli or S. aureus pathogens. E. coli was detected in 13.2% of the examined milk samples, which was comparable with previous report (15.9%) in Saudi Arabia [24]. Higher prevalence was recorded in Ethiopia (29.6%) by Garedew et al [4].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, several studies have demonstrated the activity of essential oils against pathogens in food systems [7][8][9]. In the same way, the present study shows that under the effect of M. suaveolens essential oil; there is an important abatement of S. aureus and E. coli during the storage period, these pathogens have been cited among the most incriminated in food poisoning [43][44][45][46]. In addition, the use of essential oils in food preservation makes it possible to improve the taste quality and to give a taste appreciated for the consumer [7].…”
Section: Discussionsupporting
confidence: 78%
“…In Egypt, cattle, goats and sheep are considered a potential source of E. coli infection to humans, with the important serotypes are O26, O86, O111, O126, O127, O157, O158 and O164 [34]. They shed the bacteria into the environment throughout their faeces without even suffering from clinical disease, thus allowing meat and milk contamination causing human foodborne illness following consumption of such food [35]. In this regard, Food Regulations Act stated that coliform count shouldn't exceed 1.7 log CFU/mL and E. coli shouldn't be present in even one mL of a milk sample [29].…”
Section: Discussionmentioning
confidence: 99%